Research on the equilibrium strategy of data value co-creation in water conservancy engineering projects based on differential game theory - Xiaowei An; Xi Chen; Guanghua Dong; Lingli Zhang (PLoS ONE, 2026)
Water conservancy engineering projects are characterized by long construction cycles, multiple participants, and dispersed data, resulting in low efficiency in data resource utilization. Therefore, data value co-creation is needed to enhance the value of data elements. This study develops a three-party dynamic differential game model of data value co-creation involving the contractor, designer, and owner. Both centralized and decentralized decision-making scenarios are considered, and a government subsidy mechanism is introduced to analyze multi-party collaborative decision-making behavior and its influencing factors. The results show that: (1) Under the centralized decision-making scenario, both the data value level and the total returns from data value co-creation are higher than those under the decentralized decision-making scenario. Centralized decision-making is more conducive to maximizing data value. (2) Government subsidies can increase the level of effort and returns of participating subjects, thereby incentivizing these subjects to engage in data value co-creation. (3) The cost coefficient of data value co-creation for participating parties has an inhibitory effect on their willingness to engage in data value co-creation. In contrast, an increase in the utility coefficient can significantly enhance their willingness. The research findings can provide theoretical support for data value co-creation practices in water conservancy projects and for the formulation of related policies.